2019
DOI: 10.1016/j.foodpol.2019.101762
|View full text |Cite
|
Sign up to set email alerts
|

First foods: Diet quality among infants aged 6–23 months in 42 countries

Abstract: HighlightsNutrient-dense solid foods are needed to complement breastmilk after 6 months.Data from 76,641 infants reveals which food groups are used at each age.We link intake to parental education, household wealth, climate and infrastructure.Infant feeding follows Bennett's law, also mother's schooling and local conditions.Low diet diversity in early infancy calls for new actions to meet nutrient needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 39 publications
2
28
0
2
Order By: Relevance
“…Availability and physical access emerge as key determinants of fish consumption, though often as an inference based on the location of study sites, rather than direct assessment of households’ engagement in fishing activities or opportunities for market purchases. This corresponds with several studies’ findings that a higher likelihood of children consuming fish is associated with proximity to coastal areas or inland water bodies [ 62 , 63 , 64 ]. Economic access was examined in almost two thirds of included studies.…”
Section: Discussionsupporting
confidence: 90%
“…Availability and physical access emerge as key determinants of fish consumption, though often as an inference based on the location of study sites, rather than direct assessment of households’ engagement in fishing activities or opportunities for market purchases. This corresponds with several studies’ findings that a higher likelihood of children consuming fish is associated with proximity to coastal areas or inland water bodies [ 62 , 63 , 64 ]. Economic access was examined in almost two thirds of included studies.…”
Section: Discussionsupporting
confidence: 90%
“…Agroecological and socio-economic factors played a smaller role. In LMIC, maternal education is a prevailing determinant of children's dietary diversity (Blackstone & Sanghvi, 2018;Choudhury, Headey, & Masters, 2019;Senarath et al, 2012), whereas agroecological factors show context-specific results (Choudhury et al, 2019). Moreover, a study in neighbouring Indonesia found that determinants of young children's DDS and ASF intake included mother's knowledge-combining education level and media access, as well as socio-economic status (Sebayang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our study relates to several strands of the broader literature on household resilience and nutritional effects from shocks. Reductions in income or increases in food prices have been found to lead to substitution across food categories (Choudhury et al., 2019; Hoang, 2018; Jensen & Miller, 2008) and a decrease in the quality of diets (Brinkman et al., 2010). With poor households spending a large share of their incomes on basic foods (Ivanic & Martin, 2008), this can lead to increased food insecurity and periods of malnutrition with both short‐term and long‐term health, productivity, employment, and income consequences (Akter & Basher, 2014; Niles & Salerno, 2018; Shah & Steinberg, 2017; Smith & Frankenberger, 2018; Smith & Glauber, 2019).…”
Section: Introductionmentioning
confidence: 99%